Glucose Transport and Metabolism in Sertoli Cell: Relevance for Male Fertility - R. Dias, Tania; D. Martins, Ana; P. Reis, Vania; Socorro, Silvia; M. Silva, Branca; G. Alves, Marco; F. Oliveira, Pedro (Current Chemical Biology, 2013)
Sertoli cells (SCs) are essential for the testis functional development and hence for the expression of male phenotype. They provide a unique and protected environment in testis, within the seminiferous tubules, necessary for the successful progression of germ cells into fully competent spermatozoa. SC has the ability to metabolize various substrates, but preferentially uses glucose that is converted to pyruvate and lactate. This is a crucial event since lactate is essential for germ cells survival and development due to its anti-apoptotic effect and its role as energy source. Glucose metabolism in SCs is under the complex control of several hormones, predominantly sex steroid hormones, thyroid hormones (THs): follicle- stimulating hormone (FSH) and insulin. This process may occur without the requirement of protein synthesis, suggesting a modulation of enzyme activity and/or regulation of glucose transport. The transport of glucose through the plasma membrane contributes to the modulation of lactate secretion by SCs and is mediated by specific carriers. There are two different families of glucose transport proteins: the Sodium Dependent Glucose Transporters (SGLTs) and the Glucose Transporters (GLUTs): which act in a very distinct manner. The maintenance of spermatogenesis in vivo and the male fertility capacity requires a metabolic cooperation between SCs and germ cells. Indeed, an alteration in SCs ability to metabolize glucose would be expected to compromise the energy supplies to germ cells and subsequently male fertility. Herein, we discuss the regulatory molecular mechanisms of glucose transport and metabolism in SC as well as their relevance for male fertility.
Keywords: glucose transport